A clinical trial of nicergoline to prevent temporary threshold shift. Issue 2 (25th January 2022) - Klamkam, Pana; Pagcharoenpol, Rongrat; Treesaranuwattana, Treewit; Silpsrikul, Pichayen; Jaruchinda, Pariyanan; Wasuwat, Piyalarp; Suwannahitatorn, Picha
Abstract: Objective: To evaluate the effectiveness of nicergoline to prevent temporary threshold shift (TTS) in military personnel. Study Design: A randomized control trial. Methods: Two hundred and twenty‐four participants were enrolled. Nicergoline 30 mg twice daily intake was prescribed to the study group ( n = 119) for 3 weeks. The placebo was prescribed to the control group ( n = 105) for 3 weeks, as well. Audiometric thresholds were measured at baseline and within 24 h after the participants attended a 1‐day weapons firing practice. During the firing practice, all participants had to wear foam earplugs. The TTS was assessed by using a variety of published significant threshold shift (STS) definitions. Additionally, the effects of the treatment group on the magnitude of pre‐ to postexposure threshold shifts were estimated. Tinnitus and other adverse effects of the medication were recorded. Results: The incidence of STS was 65.4% from the study group and 75% from the control group. The negative STS (thresholds improved) was 68.6% from the study group and 44.7% from the control group. The positive STS (thresholds worsened) from the study group and the control group was 31.4% and 55.3%, respectively. The effect of treatment in participants receiving nicergoline demonstrated significant coefficients (change in dB) in both ears ( p = .001). The mean different threshold of participants receiving nicergoline showed negative STS in all tested frequencies without statistical significance. However, the mean different threshold of participants receiving a placebo showed positive STS with statistical significance. Additionally, there were 16 ears detecting a warning sign of permanent hearing loss. These participants from the control group presented a longer duration of tinnitus ( p = .042). Moreover, the serious adverse effects of nicergoline were considerably low. Conclusion: The study results suggest that nicergoline may attenuate noise‐related TTS and tinnitus, and justify further investigation on the effectiveness of this drug as an otoprotectant. Level of Evidence: 2 Abstract : The temporary threshold shift (TTS) was found in the control group with statistically significant differences. The study results suggest that nicergoline may attenuate TTS and self‐reported tinnitus duration following noise exposure. Additionally, few serious adverse effects of nicergoline were shown. Further investigation on the effectiveness of nicergoline as an otoprotectant is warranted.